2002
DOI: 10.1159/000065573
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Ultrasound and Ovarian and Adrenal Hormones before and after Treatment for Hyperthyroidism

Abstract: Objective: To relate thyroid, steroid and pituitary hormones to ovarian ultrasonographic findings in hyperthyroid patients before and during treatment. Study Design: Ultrasonography of the ovaries and serum hormone determination by immunoassay were performed before and during thiamazole therapy in 18 women of fertile age treated for hyperthyroidism at the Danderyd Hospital from 1996 to 1998. Results: When hyperthyreotic, the patients had elevated serum levels of sex hormone-binding globulin (SHBG) and subnorma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…Our present findings of elevated SHBG levels in hyperthyroid children and adolescents with a normalization during ATT are in accordance with previous reports in adults [2,3,12]. In vitro studies have examined the stimulatory effect of thyroid hormones on SHBG concentrations and found a marked increase in the secretion of SHBG preceded by a similar increase in the concentration of SHBG mRNA when human hepatoblastoma cells are treated with thyroid hormones [13].…”
Section: Discussionsupporting
confidence: 93%
“…Our present findings of elevated SHBG levels in hyperthyroid children and adolescents with a normalization during ATT are in accordance with previous reports in adults [2,3,12]. In vitro studies have examined the stimulatory effect of thyroid hormones on SHBG concentrations and found a marked increase in the secretion of SHBG preceded by a similar increase in the concentration of SHBG mRNA when human hepatoblastoma cells are treated with thyroid hormones [13].…”
Section: Discussionsupporting
confidence: 93%
“…Some indicated that the reason was the increased gonadotropin concentration like LH and FSH, for the unreduced function of hypothalamic-pituitary-gonadal axis in patients with hyperthyroidism [23], which was not consistent with our study. In addition, some demonstrated that the reason was the enhanced degradation rate of cholesterol to steroid hormone, which was promoted by thyroid hormone, since steroids could convert into testosterone in adrenal [24]. Lastly, other studies considered the reason was that the thyroid hormone directly acted on the ovary, which increased the secretion of testosterone by ovaries.…”
mentioning
confidence: 99%
“…Subsequent abnormalities of various endocrine hormones are developed as a result of hyperthyroidism. Studies have confirmed that thyroid function will affect HPA axis activity, insulin sensitivity of glucose, lipid metabolism, and ovarian secretion function, resulting in hypercortisolism, insulin resistance, and sexual dysfunction (78,(98)(99)(100)(101)(102). On the other hand, patients with depression have manifested abnormalities of numerous hormones, including thyroid hormones, insulin, and sex hormones.…”
Section: Multiple Hormonal Disorders In Gd May Increase the Risk Of D...mentioning
confidence: 99%